COMPLEX NUMBERS: IN SCHOOL AND HIGHER EDUCATIONAL INSTITUTION (Scientific journal of the Fergana State University, 2023)
This article discusses the issue of the successive study of the topic "Complex numbers" in schools and pedagogical universities, in particular, in mathematical education. It is necessary to develop methods for studying newly introduced sections of mathematics, especially some recurring topics, and to improve methods of teaching academic disciplines based on new educational technologies, taking into account modern requirements and international experience. In the course of the research, various research methods were applied, namely, the study and analysis of scientific and pedagogical, methodological, mathematical literature and school textbooks in mathematics; analysis of the successive sections of the "Complex numbers"; pedagogical experiment to test the residual knowledge of students on the topic “Complex numbers”; discussion of research materials.